2009
DOI: 10.1152/jn.00047.2009
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Functional and Anatomical Architecture of the Endocannabinoid System in the Auditory Brainstem

Abstract: Zhao Y, Rubio ME, Tzounopoulos T. Distinct functional and anatomical architecture of the endocannabinoid system in the auditory brainstem. J Neurophysiol 101: 2434 -2446, 2009. First published March 11, 2009 doi:10.1152/jn.00047.2009. Endocannabinoids (ECs) act as retrograde messengers that enable postsynaptic cells to regulate the strength of their synaptic inputs. Here, by using physiological and histological techniques, we showed that, unlike in other parts of the brain, excitatory inputs are more sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 81 publications
5
62
0
1
Order By: Relevance
“…Despite early autoradiographic studies suggesting that the cochlear nucleus had the lowest expression of CB 1 receptors of any brain region (Herkenham et al, 1991), CB 1 receptors have been demonstrated to exist in the cochlear nucleus in moderate densities (Tzounopoulos et al, 2007;Zhao et al, 2009;Zheng et al, 2007). Tzounopoulos et al (2007), using immunogold labelling, have shown that CB 1 receptors are localised at the parallel fibre/cartwheel cell and parallel fibre/fusiform cell synapses in the dorsal cochlear nucleus and that they regulate synaptic plasticity such as LTD. Zhao et al (2009) went on to show that fusiform and cartwheel cells also express the enzymes, diacylglycerol lipase a and b, that are necessary for the synthesis of the endocannabinoid, 2 arachodonyl-glycerol (2-AG), which has been implicated in the regulation of epileptiform activity in other brain regions (Ludanyi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite early autoradiographic studies suggesting that the cochlear nucleus had the lowest expression of CB 1 receptors of any brain region (Herkenham et al, 1991), CB 1 receptors have been demonstrated to exist in the cochlear nucleus in moderate densities (Tzounopoulos et al, 2007;Zhao et al, 2009;Zheng et al, 2007). Tzounopoulos et al (2007), using immunogold labelling, have shown that CB 1 receptors are localised at the parallel fibre/cartwheel cell and parallel fibre/fusiform cell synapses in the dorsal cochlear nucleus and that they regulate synaptic plasticity such as LTD. Zhao et al (2009) went on to show that fusiform and cartwheel cells also express the enzymes, diacylglycerol lipase a and b, that are necessary for the synthesis of the endocannabinoid, 2 arachodonyl-glycerol (2-AG), which has been implicated in the regulation of epileptiform activity in other brain regions (Ludanyi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Tzounopoulos et al (2007), using immunogold labelling, have shown that CB 1 receptors are localised at the parallel fibre/cartwheel cell and parallel fibre/fusiform cell synapses in the dorsal cochlear nucleus and that they regulate synaptic plasticity such as LTD. Zhao et al (2009) went on to show that fusiform and cartwheel cells also express the enzymes, diacylglycerol lipase a and b, that are necessary for the synthesis of the endocannabinoid, 2 arachodonyl-glycerol (2-AG), which has been implicated in the regulation of epileptiform activity in other brain regions (Ludanyi et al, 2008). Therefore, from these studies there is reason to think that cannabinoid drugs could modulate epileptiform activity in the cochlear nucleus that might be associated with tinnitus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these two possibilities are not mutually exclusive. Moreover, given that fusiform cells exhibit multiple forms of activity-dependent synaptic plasticity (Doiron et al 2011;Fujino and Oertel 2003;Zhao et al 2009, we propose that K ir conductances are potential targets for activity-dependent, intrinsic plasticity. Future experiments examining the developmental profile and the activity dependence of K ir heterogeneity are expected to provide answers to these questions.…”
Section: Discussionmentioning
confidence: 99%
“…A second factor that could contribute to the more sluggish optical responses to parallel fiber activation is that the underlying signals may originate from glia and dendrites, whose subthreshold responses have slower time courses. Since parallel fibers exert synaptic effects on both cartwheel cells and fusiform cells (Waller et al 1996;Manis and Molitor 1996;Davis et al 1996;Fujino and Oertel 2003;Zhao et al 2009;Tzounopoulos et al 2004), some component of the optical response may have originated from dendrites of these two cell types as well as their neighboring glial cells (astrocytes). A third possibility is that a slower conduction velocity could be in part related to the use of anesthetic in vivo.…”
Section: Discussionmentioning
confidence: 99%